How online behaviour influence value formation in online services - Kokko, Jarkko (My University, 2017)
Social interaction has grown to be an important part of the information systems. The so-called social component is present in many programs, let alone in videogames, where the social aspect has grown rapidly. Many game developers integrate different social interaction tools in online video games. These tools can be variable, most often being ways to discuss with others while playing the game. Social interaction can often be associated to a membership of certain social community. This can be anything from being composed of the whole player base of certain video game, to being just a small group of friends playing games. This study aims to find out if social interaction has any influence in value formation. Research will focus to the online video games, because these often incorporate social interaction as part of the gaming experience. Social interaction can be both positive and/or negative, and the goal is to find out using the value co-creation and co-destruction framework if players can co-create or co-destroy the value of an online video game through social interaction. Research results suggests social interaction is important regarding to value formation. Research data states that each research participant have spent more time with the game because of positive social experiences, while only one reported having stopped playing certain game because of negative social experience. Besides this one case, research data suggest negative social interaction is never the sole reason to stop playing the game. Usually there are other reasons influencing this as well.
Keywords: Value formation; social interaction; online service; digital games; fi=Tietotekniikka (KTM)|en=Computer Science|; fi=Teknisen viestinnän koulutusohjelma|en=Technical Communication Programme|